Psychological problems among parents of children with congenital anomalies - Al-Maghaireh, Dua'a F.; Kawafha, Mariam Mofleh; Khatijah Lim, Abdullah *; Shawish, Najah Sami; Kamel, Andaleeb M. Abu; Basyouni, Niven Rizk (Elsevier, 2023)
Having a child with a congenital anomaly is a very stressful event that affects the whole family due to the critical and permanent needs it might impose. This study aimed to assess stress levels among Jordanian parents of children with congenital anomalies and their relationship to three factors: depression, anxiety, and somatization. A cross sectional survey was conducted at three hospitals in Jordan among 360 parents of children with congenital anomalies by using the Perceived Stress Scale and the Portuguese version of the Brief Symptom Inventory. The study found that both parents experienced high levels of stress, anxiety, and depression, although there was a significant difference in stress level between mothers and fathers, with the mothers experiencing higher stress than the fathers. The correlation between stress levels with anxiety (r = 0.763) and depression (r = 0.829) were strong and positive, while somatization was moderate (r = 0.425). In a conclusion, parents of children with congenital anomalies experience high levels of stress. Parental stress leads to many psychological problems such as somatization, depression, and anxiety.